Complicated acute appendicitis in children: the importance of stewarding antibiotic prescriptions - Ghidini, Filippo; Virgone, Calogero; Donà, Daniele; Frigo, Anna Chiara; Leon, Francesco Fascetti; Gamba, Piergiorgio (The Turkish Journal of Pediatrics, 2022)
Background. The aim was to assess the success of a three-drug regimen, consisting of cefazoline, metronidazole and gentamicine, for the antimicrobial treatment of complicated appendicitis and to investigate predictors of failure. Methods. This retrospective study included patients who had undergone appendectomy for complicated appendicitis from 2013 to 2018. The shift to second-line antibiotics was considered a failure. The choice was based upon clinical deterioration. Patients were grouped into 2 groups: localized complicated appendicitis (LCA) and extensively complicated appendicitis (ECA) for the study purpose. Univariate and multivariate analysis were performed to identify predictors of failure. Results. Ninety patients (65.2%) with LCA and 48 patients (35%) with ECA were included. Three-drug regimen failed in 50 patients (36%) with a higher rate in the ECA group (50%, p=0.017). In a multivariate analysis, this failure was found to be associated with ECA (adjusted OR 3.00 [1.2-7.4], p=0.041). Children with ECA experienced a longer hospital stay (median length 8 days, p < 0.001) and antimicrobial therapy (median length 8 days, p < 0.001). However, no difference in the rate of surgical site infections was found (p=0.514). Conclusions. The institutional antibiotic stewardship program highlighted a high failure rate for the old threedrug regimen. A new protocol should be recommended, especially for the patients affected by ECA.